Effects of probiotic isolated from saline tilapia green water against Aeromonas hydrophila infection on juvenile tilapia (Oreochromis niloticus) - Albances, Jason Orendez (Miagao, Iloilo University of the Philippines Visayas, 2021)
Aeromonas hydrophila is a major pathogen associated with serious production losses in the culture of Oreochromis niloticus. The present study was conducted to find potential probiotics from tilapia-green water that could prevent A. hydrophila infection in juvenile tilapia. Several presumptive bacterial probionts were isolated and tested against. A. hydrophila for antagonism and pathogenicity to the host fish. The isolated probiotics and prevention of infection on a pathogen challenge test. Results showed that out of eight isolates tested, Staphylococcus aureus showed the best anagonisticactivity against the pathogen and this was used in the subsequent experiments. No mortalities or disease signs were fond in juvenile tilapia after a 30-day pathogen challenge test with the isolated probiotic, S. aureus. Dietary supplementation level at 10 6 cfu/ml S. aureus prevented mortalities caused A. hydrophila infection. The application of 10 6 cfu/ml S. aureus is considered a practical approach to prevent A. hydrophila infection in the rearing of juvenile tilapia.
Thesis (MS Aquaculture) -- Miagao, Iloilo : University of the Philippines Visayas, August 2021.